2020
DOI: 10.1021/acsaelm.0c00887
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Retained Conversion of Neutral to Mixed Valence Tetrathiafulvalene Crystals through a Spontaneous Redox Reaction

Abstract: Solid-state conversion by the spontaneous redox reaction between tetrathiafulvalene (TTF) and ferric ion is employed to obtain morphology-retained TTF mixed valence (MV) salt crystals. Radical species are formed first at the surface of TTF crystals and then inside of the crystals by diffused ferric ions as revealed by the time-dependent UV−vis absorption and electron spin resonance (ESR) spectroscopy studies. The resulting TTF MV salt crystals exhibit 6 orders of magnitude higher electrical conductivity than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Highly conducting organic charge transfer (CT) complexes, represented by tetrathiafulvalene (TTF)-based ones including TTF-tetracyanoquinodimethane (TTF-TCNQ), , have received a great deal of attention for their potential roles in organic electronic applications. , To crystallize the TTF radical cation (TTF •+ ), counteranions are essential for the charge balance, resulting TTF radical salt crystal. Since the radicals can play as a pivotal charge carrier, the formation and behavior of the radicals have been an important research subject to improve their electrical conductivity. Besides the core component that possesses and transports charge carriers, counteranions that coexist in many conducting charge transfer complexes also should be carefully considered to evaluate the overall electrical property of CT complexes because counteranions, especially in the case of metal halides, are known to contribute to the electrical conductivity through back charge transfer. For example, Wudl, F. et al have shown that bismuth iodide anion contributes to the electrical conductivity of (TTF)­Pb 2 I 5 complexes through back charge transfer from the anion to TTF moieties by making them mixed valence system that is known to be a better conductor than mono valence system. , However, the back charge transfer effect from counteranions is difficult to clearly reveal as the change of anion, necessary for the evaluation of back charge transfer effect frequently involves structural changes by which the conductivity can be affected. Therefore, it is important to develop a platform system that allows systematic changes of the back charge transfer power from anions without significant structural changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Highly conducting organic charge transfer (CT) complexes, represented by tetrathiafulvalene (TTF)-based ones including TTF-tetracyanoquinodimethane (TTF-TCNQ), , have received a great deal of attention for their potential roles in organic electronic applications. , To crystallize the TTF radical cation (TTF •+ ), counteranions are essential for the charge balance, resulting TTF radical salt crystal. Since the radicals can play as a pivotal charge carrier, the formation and behavior of the radicals have been an important research subject to improve their electrical conductivity. Besides the core component that possesses and transports charge carriers, counteranions that coexist in many conducting charge transfer complexes also should be carefully considered to evaluate the overall electrical property of CT complexes because counteranions, especially in the case of metal halides, are known to contribute to the electrical conductivity through back charge transfer. For example, Wudl, F. et al have shown that bismuth iodide anion contributes to the electrical conductivity of (TTF)­Pb 2 I 5 complexes through back charge transfer from the anion to TTF moieties by making them mixed valence system that is known to be a better conductor than mono valence system. , However, the back charge transfer effect from counteranions is difficult to clearly reveal as the change of anion, necessary for the evaluation of back charge transfer effect frequently involves structural changes by which the conductivity can be affected. Therefore, it is important to develop a platform system that allows systematic changes of the back charge transfer power from anions without significant structural changes.…”
mentioning
confidence: 99%
“…The intermolecular distance of adjacent TTF moieties, affecting to the electrical property of TTF crystals, was not significantly different in both crystals. On the other hand, considering that the back charge transfer may occur through the intermolecular interaction between TTF and MCl 6 [3][4][5][6][7][8][9][10][11][12][13][14][15]16 it is also important to monitor the S•••Cl distance between S of TTF and Cl of MCl 6 3− of each crystal. They are 3.1731 and 3.166 Å in TTF 3 InCl 6 and TTF 3 SbCl 6 , respectively, which are smaller than the sum of van der Waals radii, thus, within the range of intermolecular interaction, 25 suggesting the possibility of back charge transfer from MCl 6 3− to TTF •+ .…”
mentioning
confidence: 99%